Memorandum...respecting the Belfast Congress resolution on maternity and child welfare
1930-01-28 1930 1930s 2 pages -2- of their duties to include that of selecting, reporting and supervising the foster-mothers would, in our opinion, be in the best interests of the children concerned. 5. We are of opinion that all arrangements for maternal care, including the admission of patients to maternity wards and hospitals, falls into the province of Maternity and Child Welfare Committees of Local Authorities, and that the appropriate officers to conduct all preliminary inquiries and interviews in such cases are Health Visitors, and not, as has most frequently been the practise in connection with the patients admission to the maternity wards of Poor Law hospitals, male relieving officers. 6. We suggest that, where the addition of these duties to those already performed by Health Visitors in any area is not possible without adversely affecting their present work, the difficulty can best be overcome by increasing the staff of Health Visitors, and allocating a smaller district to each, rather than by the appointment of other officers for these additional duties. Copied FC. 28th Jan., 1930 292/824/1/10